2007
DOI: 10.2320/matertrans.mb200713
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of the Phase Equilibria in the Nb-Ni-Zr System

Abstract: A thermodynamic study of phase equilibria in the Nb-Ni-Zr system has been carried out experimentally and using the CALPHAD method. To enable the thermodynamic description of the constituent binary systems, the results from a previous evaluation were adopted for the Nb-Ni, Ni-Zr and Nb-Zr systems. However, some modifications of the thermodynamic parameters of the Ni-Zr system were made based on recent experimental data on the binary and ternary phase equilibria. The phase boundaries involving the liquid phase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Tokunaga et al [68] employed thermodynamic modeling using CALPHAD methodology to determine the glassforming compositional region in the ternary Ni-Nb-Zr phase diagram; results were somewhat comparable with experimental results, but an order of magnitude lower than experimentally observed range. Density functional theory (DFT) calculations were reported as a reliable method for predictions of amorphous membranes for hydrogen permeation and purification by Hao and Sholl [69].…”
Section: Local Atomic Order In the Ni-nb-zr Alloy Membranesmentioning
confidence: 62%
“…Tokunaga et al [68] employed thermodynamic modeling using CALPHAD methodology to determine the glassforming compositional region in the ternary Ni-Nb-Zr phase diagram; results were somewhat comparable with experimental results, but an order of magnitude lower than experimentally observed range. Density functional theory (DFT) calculations were reported as a reliable method for predictions of amorphous membranes for hydrogen permeation and purification by Hao and Sholl [69].…”
Section: Local Atomic Order In the Ni-nb-zr Alloy Membranesmentioning
confidence: 62%
“…The XRD and SAD patterns confirmed the identities of these phases as shown in Figures 2 and 3, respectively. Part of the Ni-Nb phase diagram calculated by Tokunaga et al (2007) is shown in Figure 6 and the dashed vertical line denotes a binary alloy composition close to the investigated ternary alloy composition. As expected from this diagram, solidification occurs by the formation of primary Ni 3 Nb dendrites followed by the eutectic reaction producing Ni 3 Nb and Nb 7 Ni 6 .…”
Section: Discussionmentioning
confidence: 88%
“…6. Part of the binary Ni-Nb phase diagram as calculated by Tokunaga et al (2007), with an alloy composition that is close to that of Alloy 1.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The binary systems were thermodynamically investigated and used in the calculations. Three systems: Ni-Sn Gandova (2016), Liu et al (2004), Ni-Ti Gandova (2016), Tokunaga et al (2004) and Sn-Ti Yin et al (2007) exibit large number of intermediate phases.…”
Section: Introductionmentioning
confidence: 99%